Photography and the Concept of Return: A Personal View - Pietropaolo, Vincenzo (Italian Canadiana, 2021)
As a photographer of the immigrant experience, the yearning for return to a homeland has been a central theme of my research. In this paper, I explore both my personal and collective experience of displacement and uprooting (Not Paved with Gold), the annual return to Canada of temporary migrant farm workers from Mexico and the Caribbean (Harvest Pilgrims), and the metaphorical return of Italian immigrants to a spiritual homeland through the annual re-enactment of the Via Crucis on the streets of Toronto’s Little Italy (Ritual). The paper poses the question of whether the immigrant, having abandoned his homeland, can truly return to it.